2017
DOI: 10.1002/yea.3248
|View full text |Cite
|
Sign up to set email alerts
|

Many interspecific chromosomal introgressions are highly prevalent in Holarctic Saccharomyces uvarum strains found in human‐related fermentations

Abstract: In the last two decades, the extensive genome sequencing of strains belonging to the Saccharomyces genus has revealed the complex reticulated evolution of this group. Among the various evolutionary mechanisms described, the introgression of large chromosomal regions resulting from interspecific hybridization has recently shed light on Saccharomyces uvarum species. In this work we provide the de novo assembled genomes of four S. uvarum strains presenting more than 712 kb of introgressed loci inherited from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…In this context, several natural Saccharomyces hybrids have been isolated from industrial settings, such as wineries and beer fermentation tanks, demonstrating that hybrid selection based on greater fitness under fermentation conditions has already occurred. The best example is S. pastorianus ( S. cerevisiae × S. eubayanus ) and reviewed elsewhere (Gibson & Liti, ); however, many other interspecies hybrids have also been recovered (Albertin et al, ; Gonzalez, Barrio, & Querol, ; Krogerus, Preiss, & Gibson, ; Peris et al, ). For example, S. cerevisiae × Saccharomyces kudriavzevii hybrid strains were recovered in brewing environments (Gonzalez et al, ; Peris et al, ).…”
Section: Isolation and Brewing Potential Of Wild Saccharomyces Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, several natural Saccharomyces hybrids have been isolated from industrial settings, such as wineries and beer fermentation tanks, demonstrating that hybrid selection based on greater fitness under fermentation conditions has already occurred. The best example is S. pastorianus ( S. cerevisiae × S. eubayanus ) and reviewed elsewhere (Gibson & Liti, ); however, many other interspecies hybrids have also been recovered (Albertin et al, ; Gonzalez, Barrio, & Querol, ; Krogerus, Preiss, & Gibson, ; Peris et al, ). For example, S. cerevisiae × Saccharomyces kudriavzevii hybrid strains were recovered in brewing environments (Gonzalez et al, ; Peris et al, ).…”
Section: Isolation and Brewing Potential Of Wild Saccharomyces Sppmentioning
confidence: 99%
“…However, wild Saccharomyces strains with introgressions from other species do occur (Albertin et al, ; Almeida et al, ; Peter et al, )—some examples are found in S. cerevisiae with introgressions from other species including the closely related species S. paradoxus (Duan et al, ; Peter et al, ). Still, most isolates exhibiting horizontal gene transfers are generally associated with human activities: such as those found in S. uvarum , where introgressions from S. eubayanus and S. kudriavzevii were described (Albertin et al, ). These antecedents suggest that hybrids are fitter solely when associated with fermentation environments but do not persist in the wild.…”
Section: Isolation and Brewing Potential Of Wild Saccharomyces Sppmentioning
confidence: 99%
“…The following PCR program allows the amplification of all the expected fragments from the rearranged and the wild type VIII, XV and XVI chromosomes: initial denaturation at 95 °C for 15 min, followed by 35 cycles of 94 °C for 30 s, 55 °C for 90 s, 72 °C for 90 s, ending with a hold at 60 °C for 30 min. DNA templates for PCR were extracted in 96-well microplates using the previously described LiAc-SDS protocol (Chernova et al, 2018). Before analysis, PCR products were diluted 60 times in ddH 2 O and 1 μL of this solution was mixed with 0.2 μL of the internal size standard GenScanTM 1200 LIZ ® (Applied Biosystems, France) and 9.8 μL of highly deionized Hi-DiTM formamide (Applied Biosystems, France).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA of S. cerevisiae strains was quickly extracted in 96-well microplate format using a customized LiAc-SDS protocol (Albertin et al 2017). Fifteen polymorphic microsatellite loci SCAAT3 ( C3, C5, SCYOR267C, C8, C11, SCAAT2, YKL172, SCAAT6, C9, C4, SCAAT5, SCAAT1, C6, YPL009, YKL172W ) were used for estimating the genetic relationships within 96 commercial starters and the four monosporic parental strains (GN, SB, M2, F15) used in this work (S3 Table).…”
Section: Methodsmentioning
confidence: 99%